Public Funding for Energy Innovation and Decarbonization Goals: A Coherence Challenge - Ratner, Svetlana; Gomonov, Konstantin; Revinova, Svetlana (International Journal of Energy Economics and Policy, 2023)
This study is devoted to assessing the impact of public spending on research and development in the field of energy efficient technologies on achieving the goals of decarbonization and improving the energy efficiency of the economy. Using the two-stage Data Envelopment model, the study identifies countries with the highest and lowest efficiency of the national energy efficiency innovation support system. It was revealed that the most noticeable reduction in the carbon intensity and energy intensity of the economy in the medium term is demonstrated by countries that pay more attention to the introduction of organizational and social innovations related to changing consumer behavior (Brazil, Spain). Countries that are accumulating knowledge in radically new technological areas demonstrate the low efficiency of the innovation system at the implementation stage in the medium term (Japan, South Korea, US).